Risk factors associated with implant sites prepared by orthodontic treatment: a systematic review - Mohsen Taban; Arezousadat Fatemi; Milad Soleimani; Seyed Masoud Sajedi; Berahman Sabzevari (PAGEPress Publications, 2023)
The patient's health and quality of life would probably be improved with dental implant. This study aimed to evaluate the risk factors associated with dental implants place by orthodontic treatment. In this study, information on risk factors associated with implants of sites prepared, radiology stereotypes and hospitalized were obtined from databases such as Scopus, Google scholar and PubMed, and 58 articles were included for this purpose. After analyzing the articles, 24 articles were not accepted and 34 articles were accepted, then, 16 articles were miscarriage and 18 articles were scientific sources. The results showed that orthodontic treatment has a significant effect on a person's sense of beauty and would possibly increase self-confidence and quality of life. The stability of the implant in the healing phase depends on the quality and quantity of the bone. Also, the width of the bone is one of the important issues in creating a successful treatment. When an implant fails, problems and symptoms of failure usually occur within the first year after surgery. After one year, there is only about a 1% chance of failure, and on average only 1% of all implants fail each year.